Complications of Methamphetamine Use in Orthopaedic Trauma. Issue 10 (October 2020) - Carney, John; Trasolini, Nicholas; Kang, Hyunwoo P.; Nguyen, Charles; Lee, Ryan; Marecek, Geoffrey S.
Abstract : Objectives: To determine whether methamphetamine (MA) users are at an increased risk for complications compared to matched controls in the setting of orthopaedic trauma. Design: Retrospective cohort study. Setting: Academic Level-1 Trauma Center. Patients: MA users and matched controls. Intervention: MA use. Main Outcome Measurements: Infection, Deep Vein Thrombosis (DVT), and nonunion. Results: Five hundred sixty-seven patients were included in our study (189 MA users, 378 matched controls). On univariate analysis, MA users had a higher incidence of DVT (3.2% vs. 0.5%), but no statistically significant difference in infection or nonunion rates. MA users also had a higher incidence of intensive care unit admission (36.0% vs. 27.8%), leaving the hospital against medical advice (9.0% vs. 2.1%), nonadherence to weightbearing precautions (18.8% vs. 7.3%), and a higher incidence of loss of follow-up (47.1% vs. 30.4%). However, MA users had a lower incidence of surgical treatment for orthopaedic injuries (51.9% vs. 65.9%). When surgical treatment was pursued, more trips to the operating room were required for orthopaedic injuries in the MA group (2.6 vs. 1.5 trips). On multivariate analysis, MA users continued to demonstrate a higher incidence of DVT and a lower incidence of operative management, but more trips to the operating room when surgical management was pursued, a higher admission rate to the intensive care unit, and a greater incidence of loss of follow-up. Conclusions: MA use is associated with increased inpatient and outpatient complications. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.